Attitudes of patients and physicians on repeat biopsies for lung cancer. Issue 3 (4th May 2017) - Chia, Puey Ling; Devitt, Bianca; Clay, Timothy; Mclachlan, Sue-Anne; Mitchell, Paul; John, Thomas
ABSTRACT: Background : Patients are increasingly being asked to undergo repeat biopsies for both clinical and research reasons as targetable resistance mutations and molecular drivers are discovered in lung cancer. We aimed to investigate patient's and physician's attitudes towards re-biopsies in lung cancer. Methods : Patients attending the lung oncology clinic at an academic centre in Melbourne were invited to complete a questionnaire assessing their attitudes on re-biopsies. Physicians were invited to complete an online questionnaire through the Australasian Lung Trials Group (ALTG). Results : Eighty nine respondents (50 patients and 39 health professionals) completed their respective questionnaires. The most important factor in a patient's decision to undergo re-biopsy was their oncologist's recommendation (25/44, 57%). Most physicians (36/39, 92%) supported repeat biopsies to investigate for therapeutic biomarkers. 53% (20/38) of physicians were happy to recommend research-only biopsies, and 48% (22/46) of patients were agreeable to it. The majority of patients would agree to a re-biopsy in order to participate in a clinical trial 27/45 (60%) or on progression of disease to check on the resistance mechanism 32/46 (70%). Conclusions : Lung cancer patients' decisions concerning re-biopsies were strongly influenced by their oncologists' recommendations. Only about 50% of both patients and clinicians would consider a biopsy solely for research purposes.